A Distinctive Encounter With Diffuse Alveolar Hemorrhage in Granulomatosis With Polyangiitis and Pneumonia - Shrijan Shrestha; Pragya Rai; Gyan Kayastha (Clinical Case Reports)
ABSTRACT This article highlights the critical importance of identifying the classic triad of hemoptysis, anemia, and diffuse pulmonary infiltrates, offering clinicians a structured approach for the timely diagnosis and management of the diffuse alveolar hemorrhage in setting of GPA. Post‐intubation HRCT findings revealed diffuse patchy ground glass opacities in both lungs, along with right lobar consolidation showing liquefaction and an air‐fluid level.